Methodological foundations of building a system of additional education for children in Russia - Zolotareva, Angelina V. (Journal of the Belarusian State University. Sociology, 2024)
The methodological principles of building a system of additional education for children in Russia are described, namely the principles of complementarity, accessibility, personal determination, individualisation, continuity diversification, activity, self-activity, etc. The main approaches to the organisation of the system of additional education for children are listed, in particular, personality-oriented, system-activity, socio-cultural, anthropocentric, integrative-variable, polyspheric, etc. The model of the system of additional education for children in Russia is given, its main elements are shown. It is noted that this model allows us to study the social order in the field of additional education for children, determine its goals, objectives and content elements, create conditions for the implementation of pedagogical activities, and monitor the results of extracurricular education. The main trends in the development of this area are recorded.
Keywords: education system; additional education for children; methodological foundations; principles of education; approaches to education; models of organising of the system of additional education for children